A Covid Competition Dilemma: Legal and Ethical Challenges Regarding the Covid-19 Vaccine Policies during and after the Crisis - Mina Hosseini (Public Governance, Administration and Finances Law Review, 2021)
The Covid-19 pandemic has impacted multiple facets of our lives and created a number of legal and ethical dilemmas. One of the greatest challenges at present is the production and distribution of the Covid-19 vaccine. Refusing to supply Covid vaccines widely could affect millions worldwide, and the pandemic may last for a long time. The competition authorities’ monitoring of the health sector in many countries has been subject to changes in the current crisis. The question is whether we can force the Covid-19 vaccine manufacturers, legally and ethically, to sell their products and share their information with their competitors. Furthermore, what are the post-pandemic consequences of policies adopted during the pandemic? This paper employs a descriptive-analytical method to examine the importance of competition and intellectual property policies as they relate to Covid-19. It concludes that instead of focusing on individual rights in a crisis, public rights need to be emphasised. However, we should not underestimate the post-pandemic consequences of policies adopted during the Covid-19 pandemic.